Pengaruh Model Discovery Learning Berbantuan Media Video terhadap Hasil Belajar Siswa pada Materi Sistem Gerak Manusia - Pitalia, Andri; Fausan, Muhammad Mifta; Pujiastuti, Indah Panca (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aimed to determine the effect of applying the video-assisted discovery learning model on student learning outcomes on the Human Movement System material. This research employed a quasi-experimental method with a Pretest-Posttest Control Group Design. The study population was all students of class XI MIPA at SMA Negeri 2 Majene, with a sample of 34 students in the experimental group and 32 students in the control group, selected using a cluster random sampling technique. The research instrument used was a cognitive learning outcome test in the form of 30 multiple-choice questions. Data analysis was performed using descriptive and inferential statistics (Independent Samples T-Test) with the assistance of SPSS version 26. The results showed that the average posttest score of the experimental group (75.44) was significantly higher than the control group (71.97). The hypothesis test result yielded a significance value (2-tailed) of 0.002, which is less than α = 0.05. This indicates that H0 was rejected and H1 was accepted. Therefore, it can be concluded that there is a significant effect of using the video-assisted discovery learning model on student learning outcomes on the Human Movement System material.